Development and Application of Lactobacillus plantarum PSCPL13 Probiotics in Olive Flounder (Paralichthys olivaceus) Farming - Muhammad Aleem Abbas; Hae-Jung Kim; Ga-Yeong Lee; Hae-Yeon Cho; Syed Al Jawad Sayem; Eon-Bee Lee; Seung-Jin Lee; Seung-Chun Park (Microorganisms)
Aquaculture has grown significantly, contributing to global food security and sustainability; however, intensified fish farming has increased disease susceptibility and antibiotic resistance. This study assessed the probiotic potential of Lactobacillus plantarum PSCPL13 (hereafter, PSCPL13), isolated from the intestines of Japanese eels, for enhancing the health of olive flounder. After screening 16 Lactobacillus isolates, PSCPL13 was selected because of its potential broad-spectrum antibacterial activity against many pathogens, such as Vibrio and Edwardsiella. This strain exhibited high acid and bile salt tolerance, which is crucial for intestinal survival. Molecular characterisation confirmed PSCPL13 to be L. plantarum. It was resistant to all tested antibiotics and exhibited significant enzyme activity. In vivo assays in olive flounder revealed that the body weight and length of the fish were significantly higher, while the prevalence of pathogens was lower in their gut microbiota. Regarding haematological parameters, the treated groups exhibited lower eosinophil counts and higher IgM levels, suggesting enhancement of the immune system. These findings indicate that PSCPL13 is a potential probiotic that can be used in aquaculture for naturally improving fish health, growth and immunity, in addition to combating antibiotic resistance and reducing environmental impacts. These findings not only highlight the potential of PSCPL13 in sustainable aquaculture but also provide a foundation for the development of future probiotics.